EFFECT OF THE COMBINATION OF LERCANIDIPINE AND CARVEDILOL ON THE FUNCTIONAL STATE OF THE HEART IN PATIENTS WITH CHRONIC HEART FAILURE AND ARTERIAL HYPERTENSION - Imamaliev, G.M.; Nuriyev, A.A.; Kurbanova, K.I.; Amrakhova, L.K.; Bayramova, S.A.; Aliyeva, S.A.; Hadiyeva, Sh.F. (World of Medicine and Biology, 2025)
To study the effect of a combination of lercanidipine and carvedilol on heart failure, 36 patients with arterial hypertension and I–III functional state heart failure according to the New York Heart Association classification were enrolled in the study (Group A). The control group consisted of 32 patients with the same pathology (Group B). The groups were divided into subgroups (3 per group) according to the functional states I, II, and III. Subgroups from Group A received lercanidipine and carvedilol, while subgroups from Group B received only carvedilol for 6 months. After treatment, significant improvements in systolic and diastolic function parameters were observed in all subgroups from Group A (p